Lane Changing Behaviour Due To U-Turns at Uncontrolled Median Opening Using Markov Process - Rashmi N; S N Manjunath (International Journal of Scientific Research in Civil Engineering, 2022)
Multilane highways are provided with raised medians for segregating traffic direction wise. An opening in median facilitates the road user for crossing and reversing the direction of travel to access adjacent property. Control of access plays a major role in imparting highway safety. Uncontrolled median openings reduce the level of service and increases the chances of accidents due to increased conflict points. U-turning vehicles contribute to lane changing behaviour of main traffic stream thereby causing speed reduction and delay.The proposed study aims to assess the probability of lane change of two wheelers, car, LCV and HCV in main stream due to U turns at an uncontrolled median opening by applying Markov’s process. The estimated probabilities are compared with field observation. The variation in speed during the lane changing manoeuvre is studied by using Traffic Data Extractor and Kinovea software. The study reveals interesting information on the relevancy of applicability of Markov’s principle with respect to type if vehicle.
Keywords: Lane changing; Markov process; median opening U-turn; probability